COVID-19: Exposing unmatched historical disparities in the South African institutions of higher learning - Mtshweni, B. V. (South African Journal of Higher Education, 2022)
The outbreak of the COVID-19 pandemic has been on the rampage and severely affected lives of many globally. The disruption resulting from the pandemic cuts across various aspects of the society such as the economic, social, environmental and educational domains. This article specifically explores the impact of COVID-19 on the higher education system in South Africa and also delves into academic challenges experienced by students during the pandemic. The article explores students’ experiences during the pandemic in conjunction with challenges which existed in the higher education system before the advent of COVID-19 owing to the legacy of apartheid, transformational and other developmental issues in the South African context.